DISTRIBUTION AND COMPREHENSIVE DIAGNOSIS OF OPISTHORCHOSIS IN NON-COMMERCIAL CARP FISH IN CENTRAL RUSSIA - S. K. Shibitov (Российский паразитологический журнал, 2019)
The purpose of the research is studying the expansion of opisthorchosis in non-commercial fish in the Tver, Moscow, Kaluga and Yaroslavl Region rivers and lakes. Developing a comprehensive approach in the diagnostics of opisthorchosis applying morphological, molecular and genetic methods and the bioassay method.Materials and methods. The work was done in 2014–2018. 90 specimens of non-commercial fish were studied which were caught by recreational fishing in three rivers and three lakes of the central part of Russia. A metacercaria was divided using fish muscles digested in a simulated gastric fluid in the VNIIIP laboratory of sanitary parasitology. For a differentiated diagnostics of the metacercarias of trematodes, a comprehensive approach was applied in the work using the methods of morphology determination by a light microscope and professional literature, a method of bioassay on golden hamster in a vivarium, and by a polymerase chain reaction (PCR) in the VNIIIP laboratory of molecular biology. For this purpose, species-specific primers and standard commercial sets published earlier were used to divide and amplify a DNA. The reaction was detected in a 1.5% agarose gel.Results and discussion. According to the results of the completed studies, the roach from the Desna River (the Moscow Region), the Nara River (the Kaluga Region), and the roach and the silver bream from the Volga River (the Tver Region) were infected with metacercarias Opisthorchis felineus, which was evidenced by the PCR. The roach, white beam and tench from the Istra Reservoir, Lake Beloye and Lake Nero were free from metacercarias O. felineus. A bioassay test on Syrian hamsters was positive when metacercarias from muscles of the roach caught in the Desna of the Moscow Region were fed off. In other cases, the bioassay tests were negative irrespective of the PCR positive in the roach from the Nara and the roach and silver bream from the Volga. Thus, the central part of Russia currently has pestholes of opisthorchosis O. felineus in the small rivers (the Desna, the Nara) and in the Volga in and around the Tver Region. The infection intensity in the roach in the small rivers decreases with age and proceeds as a mono infection, whereas the roach and the silver beam in the Volga were infected with metacercarias of several types of trematodes, and metacercarias O. felineus in such types can be confirmed by the PCR as a bioassay at low concentrations of metacercarias of opisthorchid flukes provides little information. The roach and the tench in Lake Beloye on the east of Moscow were free from all metacercarias of trematodes, whereas some few metacercarias of trematodes that are nonpathogenic for a human being and carnivore were detected in the roach and the silver beam in the Istra Reservoir of the Moscow Region. Very few metacercarias of nonpathogenic trematodes were found in Lake Nero of the Yaroslavl Region.